Analisis Pengendalian Kualitas Produk Dengan Metode Six Sigma Pada Usaha Hj. Adawiyah Di Samarinda - Monica Lumataw; Anis Rachma Utary; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Competitionin the corporate world these days of tighter encourage companies to further develop ideas for an effective and efficient in achieving the goals and objectives have been set. Hj. Adawiyah businessis one of the producer snacks amplang kuku macan. Hj. Adawiyah business also to continuously improve product quality by suppressing the number of defectsin the manufacturing process.Â  Six Sigma is a vision of improved quality to the target 3.4 failures per million opportunities for each transaction of goods and services. So Six Sigma is a method or technique of controlling and improving the quality of which is a dramatic breakthrough in the field of quality management.Â  By using Six Sigma method scan be seen that the quality of amplang kuku macan produced by the company that is pretty good with the 3.54 sigma level of damage to 62.816 million production (DPMO). Implementation of six sigma quality improvement in this study can be concluded that there were three highest causes of product defects: amplang colour is not golden brown 49%, amplang form are crushed 28% and amplang uneven size 23%.